Trends in commuter and leisure travel in The Netherlands 1991-2001 - Mode choice and travel time - Christy Collins; Arianne De Blaeij (European Regional Science Association (ERSA), 2005)
Data collected over recent years indicates that there has been an increase in the average distance of trips made, in the Netherlands (e.g. in 1985 the average trip made was 8.7 km, in 2000 the average trip length was 10.6 km (Harms, 2003)). This paper uses a multi-level approach to look at the micro and macro level factors that affect the travel behaviour of individuals for commuting and leisure in the Netherlands over the last 10 years. A strong influence on the travel behaviour of an individual comes from the context of the household they belong to, the household operates with the context of the residential area in which they live, and all our behaviour is affected by our temporal location. The behaviour of individuals can be considered as dependent on context, and these contextual influences can be envisaged as nested. The multi-level approach allows us to simultaneously consider the impact of individual factors (such as gender), household factors (such as household income), and municipality level factors (such as local population density) and at the same time look at trends across time in commuting and leisure travel behaviour. The advantage of the multi-level approach is that it allows a wholistic approach, where not only aggregate or individual data is used to explain travel behaviour but both levels' explanatory contributions are included in analyses conducted.
Keywords: 330